Augmenting Pentose Utilization and Ethanol Production of Native Saccharomyces cerevisiae LN Using Medium Engineering and Response Surface Methodology - Sharma, Shalley; Varghese, Eldho; Arora, Anju; Singh, K.N.; Singh, Surender; Nain, Lata; Paul, Debarati (Frontiers in Bioengineering and Biotechnology, 2018)
Economics of ethanol production from lignocellulosic biomass depends on complete utilization of constituent carbohydrates and efficient fermentation of mixed sugars present in biomass hydrolysates. Saccharomyces cerevisiae, the commercial strain for ethanol production uses only glucose while pentoses remain unused. Recombinant strains capable of utilizing pentoses have been engineered but with limited success. Recently, presence of endogenous pentose assimilation pathway in S. cerevisiae was reported. On the contrary, evolutionary engineering of native xylose assimilating strains is promising approach. In this study, a native strain S. cerevisiae LN, isolated from fruit juice, was found to be capable of xylose assimilation and mixed sugar fermentation. Upon supplementation with yeast extract and peptone, glucose (10%) fermentation efficiency was 78% with ~90% sugar consumption. Medium engineering augmented mixed sugars (5% glucose + 5% xylose) fermentation efficiency to ~50% and 1.6% ethanol yield was obtained with concomitant sugar consumption ~60%. Statistical optimization of input variables Glucose (5.36%), Xylose (3.30%), YE (0.36%), and peptone (0.25%) with Response surface methodology led to improved sugar consumption (74.33%) and 2.36% ethanol within 84 h. Specific activities of Xylose Reductase and Xylitol Dehydrogenase exhibited by S. cerevisiae LN were relatively low. Their ratio indicated metabolism diverted towards ethanol than xylitol and other byproducts. Strain was tolerant to concentrations of HMF, furfural and acetic acid commonly encountered in biomass hydrolysates. Thus, genetic setup for xylose assimilation in S. cerevisiae LN is not merely artefact of xylose metabolizing pathway and can be augmented by adaptive evolution. This strain showed potential for commercial exploitation.